Health Impacts of Climate Change as Contained in Economic Models Estimating the Social Cost of Carbon Dioxide. (29th July 2021) - Cromar, Kevin; Howard, Peter; Vásquez, Váleri N.; Anthoff, David
Abstract: The health impacts of climate change are substantial and represent a primary motivating factor to mitigate climate change. However, the health impacts in economic models that estimate the social cost of carbon dioxide (SC‐CO2 ) have generally been made in isolation from health experts and have never been rigorously evaluated. Version 3.10 of the Framework for Uncertainty, Negotiation and Distribution (FUND) model was used to estimate the health‐based portion of current SC‐CO2 estimates across low‐, middle‐, and high‐income regions. In addition to the base model, three additional experiments assessed the sensitivity of these estimates to changes in the socio‐economic assumptions in the model. Economic impacts from adverse health outcomes represent ∼8.7% of current SC‐CO2 estimates. The majority of these health impacts (74%) were attributable to diarrhea mortality (from both low‐ and high‐income regions) followed by diarrhea morbidity (12%) and malaria mortality (11%); no other health impact makes a meaningful contribution to SC‐CO2 estimates in current economic models. The results of the socio‐economic experiments show that the health‐based portion of SC‐CO2 estimates are highly sensitive to assumptions regarding income elasticity of health effects, income growth, and use of equity weights. Improving the health‐based portion of SC‐CO2 estimates could have substantial impacts on magnitude of the SC‐CO2 . Incorporating additional health impacts not previously included in estimates of SC‐CO2 will be a critical component of model updates. This effort will be most successful through coordination between economists and health researchers and should focus on updating the form and function of concentration‐response functions. Plain Language Summary: The health impacts of climate change are an important factor in cost‐benefit analyses that inform policy decisions. This study shows that the values used in the currently best available economic models of climate change are not representative of the scientific understanding of the health impacts of climate change. These health functions need to be updated in order to fully account for the benefits of reducing greenhouse gas emissions. This finding supports the recent call by the US government to take concrete steps to improve how agencies consider the impacts of climate change in considering potential policy decisions. Key Points: This study assesses the incorporation of health impacts in economic models of climate change Improving the health functions in integrated assessment models will lead to a more accurate estimation of the social cost of carbon Socioeconomic factors modify the interaction between climate and health and should be considered in updates of integrated assessment models